The prevailing anthropogenic effects on certain smaller Northwestern Romanian rivers - Wilhelm Sándor (Tiscia monograph series, 2002)
In the course of the research of Barcau, Crasna and Ier rivers the particular damaging effects of the anthropogenic factors were proved and the indicator role of some fish specics came into limelight.